Beyond the first purchase: unpacking the continuance intentions behind sustainable consumption - Tong, Xiayu; Wang, Kai; Feng, Shuaiming (Frontiers in Psychology, 2025)
This study investigates the continuance behavior intention (CBI) of Chinese consumers toward green products by extending the Theory of Planned Behavior (TPB) with pre-adoption experience (PAE), environmental perception (EP), attitude (ATT), subjective norms (SN), perceived behavioral control (PBC), habit (HAB), and pro-environmental self-identity (PESI). Data from 588 respondents with prior green product experiences were analyzed using partial least squares structural equation modeling (PLS-SEM). Results show that PAE positively influences ATT, SN, and PBC. EP significantly affects ATT, SN, and PBC, while HAB is crucial for sustaining green consumption. Additionally, PESI moderates the relationships among EP, ATT, HAB, and CBI. This study highlights the importance of aligning green products with consumer identities and promoting PESI through education and incentives, which provides practical insights for fostering sustained green consumption in emerging markets.